Factors associated with receipt of Tetanus, Diphtheria, and Acellular Pertussis Vaccine (Tdap) in mothers who deliver preterm - Shetal I. Shah; David Aboudi; Daniel B. Blatt (Journal of Pediatric and Neonatal Individualized Medicine, 2023)
Background: Maternal Tetanus, Diphtheria, and Acellular Pertussis Vaccine (Tdap) vaccination is recommended to prevent pertussis in newborns. Preterm infants experience greater morbidity/mortality from pertussis. Data on Tdap receipt in mothers who deliver preterm is limited.